A simplified economic model and case study for recovery ventilation based on SPECO method. (December 2022) - Tian, Man-Wen; M. Abed, Azher; E. Anqi, Ali; Guo, Wei; Wae-hayee, Makatar; Fayed, Mohamed; Nag, Kaushik
Abstract: Covid-19 further revealed the significance of ventilation by air conditioning systems. Most common split heaters and resistance heaters recirculate the indoor air without ventilation process. Ventilation wastes energy consumption by the building. However, adding an air-to-air heat recovery unit seems a quick solution to reduce the wasted heat of the ventilation process. Nonetheless, recovery unit means further pumping power (pressure drop through the air-to-air heat exchanger), capital cost, additional fans and their electricity consumption, exergy costs and so on. Hence, the profitability of the recovery unit depends on outdoor temperature, desired indoor temperature, electricity price of the region, exergy loss and also the aforementioned factors. In this research the general standard Specific Exergy Costing theory is employed and simplified as an economic strategy for recovery ventilation. The model not only is able to predict the profitability of the ventilation process using air-to-air heat exchanger, but also it is an optimization tool for air-to-air heat recovery units as provided as a case study in this paper.